The Life and Growth of Language - Whitney, William Dwight, 1827-1894 (Cambridge : Cambridge University Press, 2013)
William Dwight Whitney (1827-94) was the foremost American philologist and Sanskrit scholar of the nineteenth century. After studying in Germany, then at the forefront of linguistic scholarship, he assumed the chair of Sanskrit at Yale in 1854, with comparative philology added to his professorship in 1869. As well as teaching modern languages, Whitney published over 300 scholarly papers and books, acted as chief editor of the ten-volume Century Dictionary, and co-founded the American Philological Association. In this important 1875 work, the influence of evolutionary theory on other branches of nineteenth-century scholarship, not merely biology, is clear in the discussion of the development of language. Whitney's survey is wide-ranging, beginning with an examination of language acquisition and how language shapes or limits our thought processes. Stressing the scientific basis of historical linguistics, he further looks at how different languages have changed over time, in terms of grammatical form, pronunciation and meaning.
Reprint. First published in 1875 by Henry S. King & Co. This digitally printed version, 2013.
Includes index.
Keywords: Language and languages